The Correlation Between Fluxes of Balmer Emission Lines of H? and H? and Colors of a Galaxy in VNIR Region - AL-Mashhadani, Layali (JOURNAL OF ADVANCES IN PHYSICS, 2019)
ABSTRACT We have studied the correlation between the flux and colors of a galaxy sample from SDSS, Data Release 13 as measured by the standard Balmer decrement technique in both visible and near-infrared region, covering the spectral region from (4500-8500) Ao. We analyzed the spectral properties of the sample in the three (g, r, i) optical bands and found that the main sample tends to be redder which gives an indication that the sample has higher metallicity or older age. We carried out the standard procedures IRAF software package to get a deeper insight into the flux in HÎ² and HÎ± wavelengths range. We have concluded that the distribution of H- Beta and H- alpha line profiles is Gaussian in the two regions. We found also a linear correlation between Balmer decrement (HÎ± /HÎ² ) in lognormal units and the rest frame colors of the sample with the best fit of 3.4764. Mean and root means square (rms) profiles of HÎ² and HÎ± shows a maximum peak in the red region at the radial velocity of 1000km/s and the profiles were high symmetry in this region.